General microemulsion synthesis of organic–inorganic hybrid hollow mesoporous silica spheres with enlarged pore size. (27th June 2019) - Sun, Yangyi; Zhang, Chengyu; Mao, Yijing; Pan, Dongyu; Qi, Dongming; Di, Ningyu
Abstract : General microemulsion synthesis of organic–inorganic hybrid hollow mesoporous silica spheres with enlarge pore size with different kinds of pore expanders. Abstract : In this study, we presented a general simple microemulsion method to synthesize monodisperse organic–inorganic hybrid hollow mesoporous silica spheres (HMNs) with enlarged pore sizes by the co-condensation of TEOS and 1, 2-bis(triethoxysilyl)ethane (BTEE). The whole process just involved acid-promoted pre-hydrolysis of TEOS and BTEE to obtain amphiphilic organosilanes to emulsify the oil droplets. Meanwhile, utilizing the composite micelles of CTAB and pore expanders such as the anion surfactant sodium salicylate (NaSaL), nonionic surfactants such as P123 and F127, hydrophobic oils such as cyclohexane (CyH) and 1, 3, 5-trimethyl benzene (TMB) to jointly construct a stable O/W microemulsion, a hollow structure could be directly obtained, which also exhibited an enlarged pore size. In addition, the diameters, shell thicknesses, and pore sizes (2.5–4.2 nm) could be controlled by adjusting the amounts of expanders. This general microemulsion method can also provide theoretical guidance for the synthesis of other hollow mesoporous spheres.